Tradeoff Study between Cost and Environmental Impact of Aircraft Using Simultaneous Optimization of Airframe and Engine Cycle - Xiao Chai; Xiongqing Yu; Yu Wang (International Journal of Aerospace Engineering)
To investigate more efficient aircraft configurations which have less environmental impact, this paper develops a multidisciplinary analysis framework integrated with the airframe and propulsion analysis modules. The characteristics for propulsion, aerodynamics, weight, performance, cost, emissions, and noise can be rapidly predicted by the framework. The impact of propulsion installation with large diameter engines on aircraft weight and drag are considered in the framework. A wide-body aircraft was taken as an example for the optimization to investigate the tradeoffs between the cost metric and the environmental performance metrics. Several cases for single objective and multiobjective optimizations were performed. In the single objective optimizations, the direct operating cost, the cumulative noise, the oxides of nitrogen emissions during landing-takeoff cycle, and the mission oxides of nitrogen emissions were considered as an objective and minimized, respectively. The different objectives resulted in designs with different airframe parameters and engine cycle parameters. In the multiobjective optimizations, the direct operating costs and environmental performances were considered as the objectives simultaneously. The optimization results were the Pareto fronts for the minimum direct operating costs and environmental performances, which illustrate the quantitative relationships between the economic metric and the environmental performances.